Connection of elongation of galaxy clusters with other properties - Mlinar, Ema (Matrika, 2022)
Galaxy clusters, the largest known virialized objects in the universe, are known to be triaxial. In this paper the triaxiality of simulated galaxy clusters and its correlation with elongation, mass, dynamical state and evolution with time are presented. Zoomed-in simulations of five different regions of a larger box were used. The projected simulated clusters are in good agreement with observations. A relation between average 2D ratio of semi-axes and maximal elongation of 3D clusters was then established, and using this a theoretical limiting value for cluster maximal elongation was found. In the second part the relation between rate of interaction of the cluster (its dynamical state) and its elongation was studied, confirming the findings by other authors. Since more massive clusters are frequently in interaction, they are on average more elongated. There is a clear trend of clusters getting on average more elongated with time. A weak correlation between time evolution of elongation and cluster final mass was found, more massive clusters are on average getting more elongated with time, while smaller clusters are getting more spherical.
Keywords: elongation; galaksije; galaxies; galaxy clusters; jate galaksij; podolgovatost